OPTIMALISASI GENERASI UNGGUL MELALUI SOSIALISASI STRATEGIS: PENGUATAN FONDASI KELUARGA SEJAHTERA DI DESA ADAT MELALUI KEGIATAN PENGABDIAN MASYARAKAT - Afdhal, Afdhal; Manuputty, Feky; Makaruku, Nathalia Debby (CV. Kalimasada Group, 2024)
This article examines a strategic approach to maximize the formation of an outstanding generation through integrated socialization. Its primary focus is on strengthening the foundation of the Family well-being in Negeri Hukurila, a traditional village, as the initial basis for developing strong individual character and potential. By integrating the principles of the Family well-being into various community engagement activities, this article highlights the importance of collaboration and active participation of the community in shaping a quality younger generation. The methodology employed involves a series of activities, such as training, group discussions, and workshops, designed to enhance awareness, understanding, and application of the Family well-being concept in daily life. The results indicate that strategic socialization in strengthening the foundation of the Family well-being can significantly contribute to the formation of character, values, and competencies of the younger generation in Negeri Hukurila. The implications of this article emphasize the need for a holistic and sustainable approach in efforts to develop a community oriented towards family welfare and the growth of an excellent generation.